2022
DOI: 10.1101/2022.11.06.515336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early-life language deprivation affects specific neural mechanisms of semantic representations

Abstract: One signature of the human brain is its ability to derive knowledge from language inputs, in addition to nonlinguistic sensory channels such as vision and touch. How does human language experience specifically modulate the way in which semantic knowledge is stored in the human brain? We investigated this question using a unique early-life language-deprivation human model: early deaf adults who are born to hearing parents and thus had delayed acquisition of any natural human language (speech or sign), with earl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…In addition, expression of the candidate genes across human brain developmental stages highlighted distinct patterns in early brain development crucial to RD as previously predicted. 11 , 12 These together rendered new approaches to the assessments and discoveries of novel loci for RD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, expression of the candidate genes across human brain developmental stages highlighted distinct patterns in early brain development crucial to RD as previously predicted. 11 , 12 These together rendered new approaches to the assessments and discoveries of novel loci for RD.…”
Section: Discussionmentioning
confidence: 99%
“…2,20 We further showed that unlike those identified from family studies, the GWAS to RD as previously predicted. 11,12 These together rendered new approaches to the assessments and discoveries of novel loci for RD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deaf individuals typically rely on sign language, or hearing devices to interact with other people. Consistent evidence suggests that sign language supports the proper development of language brain circuits in deaf participants (for recent evidence, see Cheng et al, 2023; Wang et al, 2023) and sign language proficiency is associated with higher executive functions (e.g., performance in Go/no‐go task, Simon task; Kotowicz et al, 2023). Although it has been suggested that knowing sign language can help deaf individuals to feel comfortable and less stressed in social contexts (La Grutta et al, 2023), sign language can only be used with other signing individuals and hearing aids and cochlear implants (CIs) may not always work efficiently (e.g., Orji et al, 2020).…”
Section: Introductionmentioning
confidence: 88%